Pengaruh Persepsi Kualitas Medis Terhadap Kepercayaan Melalui Kepuasan Pelanggan Klinik Seby Cirebon - Diddo Adding Adove; Mimin Sumiyati; Sujeni Sujeni; Yuli Maylena; M. Tarmizi; Firda Mokodongan (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
This study aims to analyze the effect of perceived medical quality on customer trust by considering satisfaction as a mediating variable. This study uses an explanatory research method, which focuses on explaining the relationship between variables through hypothesis testing. The population in this study were customers who used services at the Seby Clinic in Cirebon. The sampling technique was carried out using the nonprobability sampling method, using the accidental sampling approach, with a total sample of 135 respondents. Data analysis was carried out using the path analysis method. The results of the study indicate that both perceived medical quality have a significant effect on customer satisfaction and trust. In addition, customer satisfaction also has a significant impact on increasing customer trust. Furthermore, customer satisfaction acts as a significant mediator in the relationship between perceived medical quality and customer trust.